Electrophoretic patterns of sarcoplasmic proteins in carangid fishes - Verghese, Bindu; Jayasankar, P (Indian Journal of Fisheries, 2011)
The present paper reports muscle myogen patterns of four species of carangids, viz. Decapterus russelli, D. macrosoma, Selar crumenophthalmus and Megalaspis cordyla using horizontal slab polyacrylamide gel electrophoresis. The number of protein fractions (presumptive loci) in the muscle of D. russelli, D. macrosoma, S. crumenophthalmus and M. cordyla were found to be 9, 7, 6 and 5, respectively. The Rf value ranged from 21 to 84 in S. crumenophthalmus, 2 to 72 in M. cordyla, 15 to 89 in D. macrosoma and 18 to 96 in D. russelli. The difference in number of fractions, their mobility pattern and staining indicated species-specificity. With the limited number of samples used in our study, there has been an indication of intraspecific polymorphism among three species of carangids, being 3.5% in D. russelli, 13.5% in D. macrosoma and 6.6% in S. crumenophthalmus. M. cordyla showed no intraspecific polymorphism. The study reveals that protein fractions in carangids can be used as species-specific markers, which could be helpful in resolving disputes in the event of any taxonomic ambiguity